Perbandingan Filsafat Pendidikan Ki Hadjar Dewantara dan Tan Malaka dalam Konteks Pendidikan Nasional (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
ABSTRACT This article examines the philosophical foundations of education proposed by Ki Hadjar Dewantara and Tan Malaka within the context of Indonesian national education. The study employs a qualitative literature-based approach focusing on ontological, epistemological, and axiological dimensions. To strengthen the analysis, the discussion is supported by open-access Indonesian scholarly journals that interpret and elaborate Ki Hadjar Dewantara’s educational philosophy. The findings indicate that Ki Hadjar Dewantara conceptualizes education as a cultural and humanistic process aimed at nurturing human dignity and independence, while Tan Malaka views education as a rational and critical instrument for social emancipation. These perspectives demonstrate complementary contributions to the development of a national education system grounded in humanity, rationality, and social justice. Keywords: Philosophy Of Education, Ki Hadjar Dewantara, Tan Malaka, National Education